2008
DOI: 10.1099/jmm.0.47766-0
|View full text |Cite
|
Sign up to set email alerts
|

Extended phage locus typing of Salmonella enterica serovar Typhimurium, using multiplex PCR-based reverse line blot hybridization

Abstract: Salmonella enterica serovar Typhimurium (S. Typhimurium) is the commonest pathogen causing food-borne disease among humans and animals in Australia. A multiplex PCR-based reverse line blot (mPCR/RLB) system was developed to rapidly identify S. Typhimurium phage types and strains within them. The system comprised 32 biotin-labelled primer sets and 38 amino-labelled probes, based on sequences that were either phage-type-related or derived from temperate phages ST64B, P22, Gifsy-1 or Gifsy-2. The system was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
(27 reference statements)
3
15
0
Order By: Relevance
“…We performed sPCRs, using the same primers as in the mPCR, and uniformly yielded amplicons of the expected size for all VF genes with mPCR/RLB probe-pair discrepancies, suggesting that withinprobe-pair discordance resulted from sequence variation within the target region of the signal-negative probes. This was confirmed by sequencing of selected sPCR products (data not shown) and supports previous work by others (18,19,23,26,32).…”
Section: Discussionsupporting
confidence: 75%
“…We performed sPCRs, using the same primers as in the mPCR, and uniformly yielded amplicons of the expected size for all VF genes with mPCR/RLB probe-pair discrepancies, suggesting that withinprobe-pair discordance resulted from sequence variation within the target region of the signal-negative probes. This was confirmed by sequencing of selected sPCR products (data not shown) and supports previous work by others (18,19,23,26,32).…”
Section: Discussionsupporting
confidence: 75%
“…Cluster analysis revealed that isolates with the same SCCmec subtype, as defined by Milheiriço et al (21), did not always group together and that none of the 52 reference strains corresponded exactly with the six type strains, suggesting that existing SCCmec type IV subtyping methods may not be able to represent complex phylogenetic relationships for this diverse MRSA type. Weak signals were noted for some probes with a few isolates, which were likely due to minor sequence variations in the probe regions, as reported previously (28).…”
Section: Resultssupporting
confidence: 55%
“…Outbreak 1 occurred in a residential college in November 2006, when 16 cases of severe gastroenteritis were diagnosed among students and staff over 2 days (23). S. Typhimurium DT170 with MLVA profile 3-11-7-12-523 was recovered from stool samples from all of the cases.…”
Section: Selection Of Isolates and Genomic Variations Between Smentioning
confidence: 99%